2022
DOI: 10.1101/2022.02.17.480851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intramuscular mRNA BNT162b2 vaccine against SARS-CoV-2 induces robust neutralizing salivary IgA

Abstract: Intramuscularly administered vaccines stimulate robust serum neutralizing antibodies, yet they are often less competent in eliciting sustainable 'sterilizing immunity' at the mucosal level. Our study uncovers, strong neutralizing mucosal component (NT50 ≤ 50pM), emanating from intramuscular administration of an mRNA vaccine. We show that saliva of BNT162b2 vaccinees contains temporary IgA targeting the Receptor-Binding-Domain (RBD) of SARS-CoV-2 spike protein and demonstrate that these IgAs are key mediators o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 102 publications
1
6
0
Order By: Relevance
“…S1D). The lack of notable IgA production in the respiratory mucosal appeared to contrast with the detection of moderate but significant IgA responses in the saliva after mRNA vaccination (21,22). We also examined IgM in the blood and BAL and observed that, whereas detectable levels of IgM were present in the circulation of both the COVID-19-vaccinated group and prior infection cases, only prior infection elicited significantly elevated IgM responses in the BAL (fig.…”
Section: Characterization Of Respiratory Mucosal Antibody Responses A...mentioning
confidence: 94%
“…S1D). The lack of notable IgA production in the respiratory mucosal appeared to contrast with the detection of moderate but significant IgA responses in the saliva after mRNA vaccination (21,22). We also examined IgM in the blood and BAL and observed that, whereas detectable levels of IgM were present in the circulation of both the COVID-19-vaccinated group and prior infection cases, only prior infection elicited significantly elevated IgM responses in the BAL (fig.…”
Section: Characterization Of Respiratory Mucosal Antibody Responses A...mentioning
confidence: 94%
“…A recent study demonstrated that neutralizing activity of salivary IgA induced by SARS-CoV-2 infection was maintained up to 73 days after clinical symptom, but later time points (189-230 days) 67 . Salivary IgAs induced by vaccination with BNT162b2 showed similar kinetics in that the binding activity specific to the SARS-CoV-2 RBD peaked at 85-120 days post vaccination but diminished by 170-205 days 68 . Both studies demonstrated that the salivary IgAs secreted as in polymeric form (dimeric and tetrameric) were superior to confer neutralizing activity than IgGs.…”
Section: Demonstrated That Iga Enhancesmentioning
confidence: 85%
“…There is overall agreement in the literature that mRNA vaccination induces IgG responses in saliva. [24][25][26][27][28][29] However, reports on saliva IgA responses after COVID-19 mRNA vaccines have varied. Several studies have reported detectable increases in saliva IgA after initial and/or booster vaccination with COVID-19 mRNA vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 At least 2 studies that found increases in saliva IgA attempted to screen out unrecognized infections by testing for serum anti-SCV2 N IgG. 24,29 All rights reserved. No reuse allowed without permission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation